Self-Tuning Control for Synchronous Machine Stabilization - Ritonja, Jozef (Elektronika ir Elektrotechnika, 2015)
A small-signal stability problem of a synchronous generator influencing a power grid was studied. A thorough theoretical analysis of a simplified linearized model of the synchronous generator connected to an infinite bus was carried out. The described analysis pointed out disadvantages of the conventional linear power system stabilizer. In contrast to the conventional, an original self-tuning power system stabilizer was developed. This stabilizer compacts a linear quadratic regulator and a recursive least square identification method. The study involving numerical simulations and laboratory experiments reveals encouraging results with displayed advantages and feasibility of this novel approach in considered applications. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12773